LanCLs have C-glutathionylation activity with potential to trap the eliminylome - Lai, K; Galan, S R G; Zeng, Y; Zhou, H; He, C; Riedl, J; Raj, R; Liu, S; Chooi, K P; Garg, N; Zeng, M; Jones, L H; et al. (University of Oxford, 2020)
Enzyme-mediated damage repair or containment, whilst common for nucleic acids, is rare for proteins. Examples of protein damage are elimination of phosphorylated Ser/Thr to dehydroalanine/dehydrobutyrine (Dha/Dhb) in pathogenic and aging processes. Bacterial LanC enzymes use Dha/Dhb to form intramolecular C–S linkages, but the functions of their LanC-like (LanCL) counterparts in eukarya are unknown. We show that LanCLs catalyze intermolecular addition of glutathione (GSH) to Dha/Dhb in proteins, driving irreversible protein C-glutathionylation. In vitro chemo-enzymatic methods were developed to site-selectively incorporate Dha/Dhb at phospho-regulated sites in kinases. Strikingly, in archetypal human MAPK-MEK1 such ‘elimination damage’ generated activated kinases (>20% full activation). This unexpected damage-mediated activation was deactivated by LanCL-mediated C-glutathionylation. Surveys of eliminated proteins (the eliminylome) suggest damage by phosphate elimination as a potential source of non-dynamic disregulation of kinase activity. LanCLs can remove these reactive electrophilic structures (the eliminylome), and their potentially deleterious or disregulatory effects, from the proteome.